Pengaruh Gaya Kepemimpinan dan Iklim Organisasi Terhadap Kinerja Pegawai di Puskesmas Suradita Kabupaten Tangerang - Siti Fauziyyah; Juliannes Cadith (Epistemik: Indonesian Journal of Social and Political Science, 2023)
This research focused on knowing the effect of leadership style on employee performance, the effect of organizational climate on employee performance, and the effect of leadership style and organizational climate on employee performance at Suradita Health Center, Tangerang Regency. This research uses an associative method with a quantitative approach. The sampling technique used saturated sampling technique, namely all Suradita Health Center employees totaling 65 people. Data collection using a questionnaire in paper form distributed to all employees. Data processing uses multiple linear regression with the help of SPSS 24 to determine the effect of the independent variable on the dependent variable. The test results show that the significance probability value for the effect of leadership style (X1) on employee performance (Y) is 0.365> 0.05 and the calculated t value is 0.913 < t table 2.297 which means that partially the leadership style has no significant effect on employee performance, then the significance probability value for the effect of organizational climate (X2) on employee performance (Y) is 0.000 000 < t table 2.297 which means that partially the organizational climate has no significant effect on employee performance, 297 which means partially the organizational climate has no significant effect on employee performance, then the probability value of significance for the effect of leadership style (X 000 297 which means partially the organizational climate has a significant effect on employee performance and the significance value for the effect of leadership style (X1) and organizational climate (X2) simultaneously or together on employee performance (Y) of 0.000 <0.05 and the value of F count 81.680> F table 3.143, it can be concluded that there is an effect of leadership style and organizational climate simultaneously on employee performance.